(untitled) (Global Journal of Science Frontier Research, 2018)
Importance of mathematical equations was discussed in this effort. Mathematical formulae calculated instrumental out puts and experimental out comes from various electro analytical techniques such as cyclic voltammetry, stripping voltammetry and controlled potential electrolysis are mentioned in this study. In addition to that statistical equations used in estimations and determinations carried by standard addition method and differential methods also discussed.